Supporting Method of the Bolted Strata in Large Deformation Roadways - Shuangsuo Yang (International Conference on Ground Control in Mining, 2005)
Based on field observations and physical modeling of simulated materials, the dynamic equilibrium principle on the whole interaction process between the surrounding rocks and support of large deformation roadways in coal mines has been developed. It explains the methods of forming the bolted strata and its changing load capacity with deformation. It also points out the factors and conditions for forming the bolted strata as follows: (1) many entries in coal mines are subject to large deformation. During their service life, it goes through the following process, elastic > plastic > fiacture > broken > loosening, etc. During this dynamic process, the mechanisms of supporting structure are changing and therefore the interaction between support and rocks experiences a process of dynamic equilibrium. Furthermore, the required supporting force for stabilizing the surrounding rocks shows overall decreasing trend; (2) the bolted strata is a special supporting structure consisting of bolt, rock skin protection devices and rock strata within the bolted horizon. As deformation increases, the supporting structure of the broken strata within the bolted horizon experiences a process of periodic change, from equilibrium > not equilibrium > equilibrium. Corresponding to this change, the supporting capacity of the bolted strata also fluctuates and gradually decreases; (3) under the bolted strata, the stability of a large deformation roadway is dynamic and step-wise; and (4) the formation of bolted strata, especially bolted broken strata depends on the existence of compressive force. Supporting the bolted strata is not constrained by the quality of the surrounding rocks. It has broad range of application.